Investigation into the magnetic immobilization of lipase and its application in the synthesis of structured triacylglycerols. (15th January 2023) - Peng, Yue; Wang, Minghao; Huang, Xianhui; Yang, Fuming; Shi, Yongge; Liao, Changbao; Yu, Dianyu
Abstract: In this paper, sn-1, 3-specific lipase from Rhizomucor miehei (RML) was immobilized with dialdehyde starch (DAS) as a support activating agent and nano-sized Fe3 O4 as a magnetic carrier. The structured triacylglycerol as human milk fat substitutes enriched with OPO was produced. The results showed that the fixed load of lipase was 52.41 mg/g. The enzyme activity recovery was 57.82%. Compared with free lipase, the relative enzyme activity of RML immobilized in magnetic particle was kept at 92% when placing 10 h in a methanol solution. The lipase immobilized in magnetic particle had an average particle diameter of 169 nm and was applied in the synthesis reaction of 1, 3-dioleoyl-2-palmitoylglycerol (OPO) by using tripalmitin (PPP) and oleic acid (OA) as raw materials. Under the optimal reaction conditions of 10% immobilized lipase, 5:1 substrate molar ratio (OA/PPP), 50 °C reaction temperature and 7 h reaction time, the product's OPO content was 43.97%, and the content of triacylglycerols rich in palmitic acid at the sn-2 position was 83.32%. After eight repeated uses at 50 °C, the relative activity of RML immobilized in magnetic particle remained above 71%. The synthesized OPO has potential to be used in infant formulas. Highlights: Lipase was immobilized with dialdehyde starch and nano-sized Fe3 O4 . Content of sn-2 palmitic acid was 83.32%, using immobilized lipase as catalyst. 1, 3-dioleoyl-2-palmitoylglycerol was 43.97%, immobilized lipase as catalyst. After 8 times of repeated use, relative activity of lipase remained above 71%.